Exploring the Students Experiences with Speaking Anxiety at Tadulako University - A. Putri Tiara; Mochtar Marhum; Desrin Lebagi; Hastini Hastini (Journal of English Language and Education, 2026)
Speaking anxiety is a common challenge that affects students’ confidence, participation, and oral performance in English language learning. Although previous studies have identified the causes and levels of speaking anxiety, limited attention has been given to students lived experiences and how they cope with anxiety in authentic classroom contexts. Understanding these lived experiences is essential because it provides deeper insights into the emotional and contextual factors that influence students’ willingness to communicate and enables educators to develop more responsive pedagogical practices. This study aimed to explore English Education students lived experiences of speaking anxiety at Tadulako University using a qualitative phenomenological approach. Data were collected through in-depth semi-structured interviews with three fourth-semester students and analyzed using Colaizzi’s Seven-Step Phenomenological Method. Four major themes emerged: sources of speaking anxiety, emotional responses during speaking activities, coping strategies, and the role of classroom support. The findings revealed that speaking anxiety was influenced by fear of making mistakes, lack of confidence, limited vocabulary, classroom atmosphere, classmates’ reactions, and lecturer expectations. Students managed their anxiety through positive thinking, careful preparation, repeated practice, and AI voice chat applications, highlighting the interaction between psychological and instructional factors in shaping speaking experiences.